2013
DOI: 10.1002/grl.50982
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved and particulate organic carbon fluxes from an agricultural watershed during consecutive tropical storms

Abstract: [1] Low-frequency high-magnitude hydrologic events mobilize a disproportionate amount of dissolved organic carbon (DOC) from watersheds, but few studies measure the role of extreme storms in exporting organic carbon from croplands. We use high-resolution measurements of storm runoff to quantify DOC and particulate organic carbon (POC) fluxes from an agricultural field during consecutive tropical storms that delivered 41 cm of rainfall to the Virginia Coastal Plain. Over a 2 week period, we measured exports of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…Our results clearly showed that the export of organic carbon was enhanced by storm events and the effect was stronger with a higher rainfall (event 2), similar to previous studies. It may result from the changes in the water flow paths to upper organic-rich horizons (Fellman et al, 2009;Kim et al, 2010;Caverly et al, 2013;Strohmeier et al, 2013;Yang et al, 2013a). In addition, while DOC was the main form of organic carbon exported in baseflow, POC became more important in the peak flow (Fig.…”
Section: Dom Quantitymentioning
confidence: 97%
See 1 more Smart Citation
“…Our results clearly showed that the export of organic carbon was enhanced by storm events and the effect was stronger with a higher rainfall (event 2), similar to previous studies. It may result from the changes in the water flow paths to upper organic-rich horizons (Fellman et al, 2009;Kim et al, 2010;Caverly et al, 2013;Strohmeier et al, 2013;Yang et al, 2013a). In addition, while DOC was the main form of organic carbon exported in baseflow, POC became more important in the peak flow (Fig.…”
Section: Dom Quantitymentioning
confidence: 97%
“…There are a variety of indices from absorption and fluorescence spectroscopy for characterizing the DOM quality, such as specific UV absorbance (SUVA), absorption spectral slope for the average molecular weight, humification index (HIX), and biological index (BIX) and fluorescence index (FI) for the DOM source (McKnight et al, 2001;Weishaar et al, 2003;Helms et al, 2008;Huguet et al, 2009). These spectroscopic indices also showed notable variations in storm events (Hood et al, 2006;Saraceno et al, 2009;Nguyen et al, 2010Nguyen et al, , 2013Inamdar et al, 2011;Yoon and Raymond, 2012;Caverly et al, 2013). However, few studies have incorporated spectroscopic DOM indices into EMMA for quantifying the contributions of various sources to the stream DOM.…”
Section: Introductionmentioning
confidence: 97%
“…However, it was obvious that the SUVA values of the raw water were higher in summer than in other seasons (ANOVA p<0.001), suggesting that there might be an influence of terrestrial inputs of enriched aromatic carbon from the tributaries (Dong et al 2014) (Fig 1). There were many reports demonstrating that soil-derived DOM exported from terrestrial environments during storms likely contains more aromatic moieties than the indigenous DOM in streams (Nguyen et al 2013;Caverly et al 2013;Yang et al 2015a). Figure 3 shows the representative SEC chromatograms detected by OCD and UVD for the DOM samples collected from Fig.…”
Section: Resultsmentioning
confidence: 97%
“…During storm events, it may represent a large flux of water (Delpla et al, 2011) contributing a large amount of DOC and POC to the stream (Caverly et al, 2013). Another potential surface source is litter leachate.…”
Section: Are These Modifications Recorded In the Stream Dom?mentioning
confidence: 99%